Macroeconomic news and bond market volatility1We thank Walter Toshi Baily, Bob Korajczyk, Jim Poterba, Mark Watson, seminar participants at the University of Chicago, Columbia University, Cornell University, and the University of Montreal, and especially Ludger Hentschel (the referee) for helpful comments. We also thank Mark Mitchell for supplying data, and Amy C. Ko and Sydney Ludvigson for research assistance. Lamont was supported by the FMC Faculty Research Fund at the Graduate School of Business, University of Chicago. A portion of this research was completed while Lumsdaine was a National Fellow at the Hoover Institution. We also thank the Financial Research Center at Princeton University for support. A previous version of this paper circulated as `Public Information and the Persistence of Bond Market Volatility'.1 - Jones, Charles M.; Lamont, Owen; Lumsdaine, Robin L. (Journal of Financial Economics, 1998)
We examine the reaction of daily Treasury bond prices to the release of U.S. macroeconomic news. These news releases (of employment and producer price index data) are of interest because they are released on periodic, preannounced dates and because they are associated with substantial bond market volatility. We investigate whether these nonautocorrelated announcements give rise to autocorrelated volatility. We find that announcement-day volatility does not persist at all, consistent with the immediate incorporation of information into prices. We also find a risk premium on these release dates.